Analysis of Socio-Economic Drivers of Cattle Grazing and Grass Harvesting in the Mount Kenya West Protected Forest, Kenya (African Multidisciplinary Journal of Research, 2022)
Management of community utilization of protected resources in protected forests is a huge challenge, particularly in the Mount Kenya region because of limited research data on the dynamics and characteristics of households living adjacent to protected forests. This research, conducted in the Mount Kenya West protected forest, sought to examine household perceptions on the different sources of pasture and fodder, to assess the significant household characteristics in driving smallholder farmers dependence on protected forests for pasture and to assess the significance of household characteristics in driving smallholder farmers’ dependence on protected forests for grass harvesting for livestock fodder. The research followed a cross-sectional research design with smallholder farmers dwelling adjacent to three forest blocks, namely, Kahurura, Hombe, and Chehe as the target population. The data was collected from May to October 2019. Questionnaires were used to collect data from a sample of 453 participants. Multiple logistic regression was used to assess the significant household characteristics in driving forest dependence cattle grazing and grass harvesting. Results obtained revealed that significant household characteristics driving forest dependence for pasture were the ownership of zero-grazing unit (p=0.03 < 0.05), the proportion of cattle under zero grazing (p=0.04 < 0.05) and proximity to the forest (p=0.08